The ability of oyster mushroom in improving nutritional composition, β-glucan and textural properties of chicken frankfurter - Wan Rosli, W. I.; Nor Maihiza, M. S.; Raushan, M. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
This study was focused on the effect of incorporation of oyster mushroom, Pleurotus sajorcaju (PSC) powder to partially replace chicken meat in frankfurters on nutritional composition, β-glucan content and textural properties. The frankfurters were formulated with either 0 (control), 2, 4 or 6% of PSC powder. The results show control chicken frankfurter had the highest fat content (11.60%) while 6% PSC frankfurter had the lowest value (10.74%). In other nutrient, ash, moisture and carbohydrate content in all samples ranged from 1.55 to 1.92%, 59.36 to 61.98% and 8.84 to 13.09%, respectively. Apparently, total dietary fiber of chicken frankfurter was increased in line with the levels of PSC powder (0.08 - 6.20%). All samples recorded β-glucan in the range from 0.16 to 1.43%, except for control sample. The texture profile showed that both adhesiveness and cohesiveness attributes were not significantly different among all mushroom-based frankfurters. However, frankfurter added with 6% mushroom was more cohesive and springier than the control formulation. In summary, partial replacement of chicken meat with PSC powder resulted in enhancement of dietary fibres up to 6.20% and β-glucan up to 14.30% significantly, lowering fat content but unchanged adhesiveness and cohesiveness attributes. Therefore, PSC powder can be considered to be used as an alternative functional ingredient to improve nutritional values of processed food products.